Radiotherapy in the treatment of extracranial hemangiopericytoma/solitary fibrous tumor: Study from the Rare Cancer Network. (March 2020) - Krengli, Marco; Cena, Tiziana; Zilli, Thomas; Jereczek-Fossa, Barbara A.; De Bari, Berardino; Villa Freixa, Salvador; Kaanders, Johannes H.A.M.; Torrente, Sara; Pasquier, David; Sole, Claudio V.; Lutsyk, Myroslav; Dincbas, Fazilet O.; et al.
Highlights: Radiotherapy improves LC and DFS in operated extremities/superficial trunk HPC/SFT. Radiotherapy should be considered after resection of extracranial HPC/SFT. Margin status could influence LC, DFS and MFS in extracranial HPC/SFT. Maximum tumor diameter could influence OS, DFS and MFS in extracranial HPC/SFT. Pathological grading could influence DFS in intra-thoracic/retroperitoneal HPC/SFT. Abstract: Background and purpose: The role of radiotherapy (RT) in the treatment of hemangiopericytoma/solitary fibrous tumor (HPC/SFT) is still under debate. We aimed at investigating whether radiotherapy can improve the results in patients operated for extracranial HPC/SFT. Materials and methods: Data from patients with HPC/SFT, treated from 1982 to 2012, were retrospectively reviewed within the Rare Cancer Network framework. Actuarial local control (LC), disease-free survival (DFS), metastasis-free survival (MFS) and overall survival (OS) were calculated with Kaplan-Meyer method. Patient and tumor parameters were analyzed by univariate and multivariate analysis. Results: Of 114 HPC/SFT, 58 (50.9%) occurred in the extremities/superficial trunk and 56 (49.1%) in intra-thoracic/retroperitoneum. Seventy-eight patients (68.4%) underwent surgery only (Sx), and 36 (31.6%) Sx and RT (Sx + RT). Median RT dose was 60 Gy (range 45–68.4 Gy) in 1.6–2.2 Gy fractions. In the extremities/superficial trunk group of patients, actuarial 5-year LC rates were 50.4% after Sx and 91.6% after Sx + RT ( p  < 0.0001) for LC, and 50.4% after Sx and 83.1% after Sx + RT ( p  = 0.008) for DFS. In the intra-thoracic/retroperitoneum group of patients, actuarial 5-year rates were 89.3% after Sx and 77.8% after Sx + RT ( p  = 0.99) for LC, and 73.8% after Sx and 77.8% after Sx + RT ( p  = 0.93) for DFS. At multivariate analysis, the addition of RT resulted in better LC and DFS in the whole series. The advantage was confirmed for LC in the group of patients affected by extremity/superficial trunk tumors. Conclusion: Addition of RT to Sx could improve the prognosis, in terms of LC and DFS, essentially in patients with extremities/superficial trunk tumor locations.